2022
DOI: 10.12688/f1000research.106950.2
|View full text |Cite
|
Sign up to set email alerts
|

The genetic causes of male infertility: a Middle East and North Africa perspective

Abstract: Male infertility is attributable to 60% of total infertility cases and about 30-50% of these cases remain idiopathic. In the Middle East and North Africa region (MENA), male infertility affects about 22.6% of men of reproductive age. Male infertility is caused by a variety of factors, including endocrine disruption, exposure to toxins, lifestyle, genetic and epigenetic modifications. Genetic modifications, including chromosomal abnormalities, chromosomal rearrangements, Y chromosome microdeletions and single-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Previous studies have identified plausible risk factors to include epidemiological factors [ 11 , 12 ], behavioural factors (smoking, alcohol, etc.) [ 11 , 13 ], genetic factors [ 14 , 15 ], and exposures to environmental toxins [ 16 , 17 , 18 ]. Our recent scoping review of published studies [ 19 ] summarized the leading risk factors associated with male infertility in Africa as “biological/physiological/genetic, behavioural/lifestyle, environmental factors, and sociodemographic risk factors”.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified plausible risk factors to include epidemiological factors [ 11 , 12 ], behavioural factors (smoking, alcohol, etc.) [ 11 , 13 ], genetic factors [ 14 , 15 ], and exposures to environmental toxins [ 16 , 17 , 18 ]. Our recent scoping review of published studies [ 19 ] summarized the leading risk factors associated with male infertility in Africa as “biological/physiological/genetic, behavioural/lifestyle, environmental factors, and sociodemographic risk factors”.…”
Section: Introductionmentioning
confidence: 99%
“…Infertility might affect 15% of couples worldwide, which refers to the inability of naturally bearing children for 1 year or longer after marriage without contraception [ 1 , 2 ]. About 60% of infertility is caused by male factors [ 3 ].…”
Section: Introductionmentioning
confidence: 99%